HTRA1 rs11528744, BCRA1 rs9928736, and B3GLCT rs4381465 are associated with age-related macular degeneration in a Chinese population - Huang, Guo; Li, Huan; Lai, Shuang; Xiao, Jialing; Wang, Liang; Xu, Huijuan; Lei, Chuntao; Zhang, Jinglan; Yu, Man; Shuai, Ping; Liu, Yuping; Shi, Yi; et al. (Frontiers in Genetics, 2022)
Purpose: Age-related macular degeneration (AMD) is a leading cause of vision loss. A Previous study based on the co-localization analysis of the genome-wide association study (GWAS) and eQTL genetic signals have reported that single nucleotide polymorphisms (SNPs), including rs760975, rs11528744, rs3761159, rs7212510, rs6965458, rs7559693, rs56108400, rs28495773, rs9928736, rs11777697, rs4381465 are associated with AMD in Americans. The aim of this study was to investigate the association of these SNPs in a Han Chinese population. Methods: There were 576 patients with AMD and 572 healthy controls collected in this study. All SNPs were genotyped by flight mass spectrum. Hardy–Weinberg equilibrium was applied to evaluate allele distributions for both AMD and control groups. The genotype and allele frequencies were evaluated using the χ2 tests. Odds ratio (OR) and 95% confidence intervals (95% CI) were calculated for the risk of genotype and allele. Results: Three of the 11 SNPs (rs11528744 in HTRA1、rs9928736 in BCRA1 and rs4381465 in B3GLCT) were found to be significantly associated with AMD in the allelic model (corrected P=0.000, OR=1.391, 95%CI=1.179-1.640 for rs11528744; corrected P=0.004, OR=0.695, 95%CI=0.544-0.888 for rs9928736; corrected P=0.002, OR=0.614, 95%CI=0.448-0.841 for rs4381465). There were no differences for the remaining eight SNPs between AMD cases and healthy controls. Conclusion: Our results showed that HTRA1 rs11528744、BCRA1 rs9928736 and B3GLCT rs4381465 were associated with AMD, suggesting that HTRA1, BCRA1, and B3GLCT genes may be involved in the development of AMD.